Dehydrating microhabitats increase mite activity and intensify ectoparasitism of Drosophila - Joshua B. Benoit; Gabrielle LeFevre; Joy Bose; Ann Miller; David Lewis; Hailie Talbott; Chandrima Das; Emily Susanto; Lyn Wang; Oluwaseun M. Ajayi; Shyh-Chi Chen; Michal Polak (Journal of Comparative Physiology B, 2026)
Parasites interact with their host in variable environments that are often subject to water scarcity and dehydration. Drosophilid fruit flies and associated ectoparasitic mites interact across a range of microhabitats, typically in decaying organic matter, such as fallen fruit and cactus tissue, that dries out and deteriorates over periods ranging from days to months. Here, we report that mite parasitism of Drosophila increases with exposure to increasingly dry conditions for two fly-mite systems ( D. nigrospiracula-Macrocheles and D. melanogaster-Gamasodes ). In D. melanogaster , artificial selection for increasing behavioral resistance did not eliminate this effect, as previously selected lines remained relatively more resistant than non-selected controls even under dry conditions. Water balance assays confirmed that mites became dehydrated when held under dry conditions, which was also associated with increased mite activity. Exposure of D. melanogaster to mites dehydrated by exposure to low relative humidity increased parasitism, further supporting that prevalence of infestation intensifies under dry conditions. The results indicate that ectoparasitism in this system is affected by the water content of the mites. The increased motivation of mites to parasitize flies under dry conditions may serve to replenish mite water stores and facilitate dispersal to more favorable microhabitats.